An unusual neck swelling in a child - Jayalaxmi Shripati Aihole (Elsevier, 2022)
Lipoblastoma is rare tumour of embryonic white fat cells, mostly seen in children less than 3 years of age presenting as a painless enlarging mass in the extremities and trunk; rarely seen in head and neck region. Here is a report of rare case of neck swelling in a child.